Value Chain Analysis OF Groundnut in South Kordofan State-Sudan (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research aims to fully analyze the value chain of the Groundnut crop produced in rainfed agriculture in Al Quoz locality - South Kordofan State - Sudan for the 2021/2022 season, starting from the local producer and reaching the final consumer. The study also provides an analysis and preparation of a detailed value chain that shows all the main actors, vertical relationships and connections that control the processes within the value chain of this crop in all its aspects.The importance of this research comes as Groundnut are considered a major economic agricultural product in the first place, and are among the oilseeds and important cash commodities in Sudan, as they rank first in production and export for the Arab and African world. Interest in this crop has increased locally due to its use in the oil and feed industry, in addition to Groundnut consumption locally, as it is used in many industries, and this is done in the irrigated and rainfed sectors. It is necessary to maximize the market value of this crop, especially in light of the climate changes that affect the safety and quality of the Sudanese product, and to preserve its position globally (Reports of the Ministry of Agriculture for the year, 2021). The concept of value chain analysis for an organization is a group of interconnected activities, and the links between those activities represent important sources for a competitive advantage and provide opportunities to achieve the common ideal of these activities. The term (value) refers to the value that is achieved for the customer at the end of providing the service.But the problem lies in the fact that the Ministry of Industry and Trade has established new instructions allowing the trade in Groundnut in accordance with Sudanese specifications and standards. According to this decision, it has also been prohibited from storing peanuts for the purpose of controlling their price and quantity, except for industrial purposes approved by official government agencies in accordance with controls and laws (Ministry of Industry and Trade, 2020) Therefore, this research comes to identify the basic functions of the Groundnut value chain, starting from providing production factors, moving to production, assembly, storage, marketing, manufacturing, and selling for export. And the number of actors at each stage of the value chain (Intisar, 2014).This research will cover: introduction, main and secondary objectives, importance, research problem, theoretical framework of some concepts related to the Groundnut crop, research method, analysis, and sources for obtaining data, developing some recommendations and proposals, and a list of sources